Chromosome aberration associated with hippocampal impairment. (30th August 2016) - Haussmann, Robert; Meissner, Gisa; Linn, Jennifer; Hackmann, Karl; Betcheva-Krajcir, Elitza; Tzschach, Andreas; Donix, Markus
Highlights: A young man presented with severe memory impairment and orientation deficits. Magnetic resonance imaging revealed bilateral hippocampal sclerosis. Cytogenetic analyses showed a complex rearrangement on chromosome 2.